Laminate and packaging bag
Patent Information
- Application Number
- JP2024061003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-04-04
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-11-16
AI Technical Summary
【0012】 本開示によれば、リサイクル性に優れるとともに、最表面に設けた表面層の耐熱性及び密着性にも優れる、積層体を提供できる。また、本開示によれば、該積層体を備える、包装袋を提供できる。
Smart Images

Figure 0007632723000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate and a packaging bag. [Background technology]
[0002] Conventionally, resin films made of resin materials have been used as constituent materials of laminates used in packaging materials. For example, resin films made of polyolefins have appropriate flexibility and transparency as well as excellent heat sealability, and are therefore widely used in laminates for packaging materials.
[0003] Generally, resin films made of polyolefin are difficult to use as a substrate for a packaging laminate because of their inferior strength, and are therefore used as a substrate by laminating them with resin films made of polyester or polyamide, etc. For this reason, typical packaging laminates are composed of a laminate in which the substrate and the sealant layer are made of different materials (for example, Patent Document 1).
[0004] In recent years, with the growing demand for the creation of a recycling-oriented society, packaging materials with high recyclability are in demand. However, conventional laminates for packaging materials are composed of different resin materials as described above, and since it is difficult to separate each resin material, they are not currently recycled. Therefore, laminates for packaging materials that have both the substrate and the sealant layer made of polyolefin films and have improved recyclability have come to be used. For example, Patent Document 2 describes a laminate in which the substrate is made of a stretched polyolefin film and the sealant layer is made of an unstretched polyolefin film. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-202519 A [Patent Document 2] JP 2020-40253 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the base material of a polypropylene film, which is a type of polyolefin film, is inferior in heat resistance to the base materials of polyester film and polyamide film. For example, when a predetermined print is applied to one side of a polypropylene film by gravure printing or flexographic printing and then cured by heat drying to form a printed layer, the polypropylene film may melt due to heat, and there is still room for improvement in laminates for packaging materials with improved recyclability.
[0007] In addition, when a substrate is printed to produce a laminate for packaging materials, reverse printing is generally performed to print on the inner surface of the substrate. Since the printed layer formed by reverse printing is located between the substrate and the sealant layer, there is a problem that the manufacturing process of the laminate for packaging materials becomes complicated when an individual image is to be displayed by reverse printing. Furthermore, when reverse printing is performed on a substrate of polypropylene film, the lamination strength may decrease when the printed surface of the substrate and the sealant layer are bonded together with an adhesive or the like.
[0008] In order to address the problems of the complicated manufacturing process and the deterioration of laminate strength, surface printing, which prints on the outer surface of the substrate, has also been considered. Inkjet printing can be mentioned as a method of displaying individual images by surface printing. UV-curable ink has been used for this inkjet printing. However, when surface printing is performed on a polypropylene film substrate by inkjet printing using UV-curable ink, there is a problem that the surface layer formed by printing is easily peeled off. In addition, even if UV-curable ink is cured by UV, the monomer may not be completely polymerized and may remain in the ink, and the residual monomer causes the hygiene of the packaging material laminate to be impaired. Furthermore, since the surface layer formed by surface printing is located on the surface of the packaging material laminate, it is easily exposed to heat from the outside, and there is a problem that migration (a phenomenon in which the components constituting the ink are dissolved from the surface layer and the image becomes blurred) is easily caused by heat from the outside in the surface layer formed by the conventional technology.
[0009] Accordingly, an object of the present disclosure is to provide a laminate having excellent recyclability and excellent heat resistance and adhesion of a surface layer provided on the outermost surface. Another object of the present disclosure is to provide a packaging bag including the laminate. [Means for solving the problem]
[0010] The present inventors have found that a surface layer can be formed on a substrate without curing by thermal drying by printing a predetermined electron beam curable resin composition on the substrate by inkjet printing and curing the electron beam curable resin composition by irradiation with an electron beam to form a surface layer. The present inventors have also found that the surface layer is less susceptible to migration due to external heat, can improve the heat resistance of the surface layer, and has excellent adhesion to a substrate made of polypropylene. The present disclosure has been completed based on these findings and through further investigation.
[0011] The present disclosure is solved by the following embodiments. <1> A laminate comprising, in this order, a surface layer, a first substrate, a first adhesive layer, and a sealant layer, the surface layer is composed of a cured product of an electron beam curable resin composition containing a polymerization initiator (A) and a polymerizable compound (B); the polymerization initiator (A) is a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, The first base material comprises a stretched base material composed of a resin composition mainly composed of polypropylene, The sealant layer is made of a resin composition containing polypropylene as a main component. <2> The content of the polymerization initiator (A) in the electron beam curable resin composition is 0.1% by mass or more and 2% by mass or less. <1> The laminate according to claim 1. <3> The electron beam curable resin composition further contains an amine having a molecular weight of 500 or more. <1> or <2> The laminate according to claim 1. <4> The content of the amine in the electron beam curable resin composition is 0.1% by mass or more and 2% by mass or less. <3> The laminate according to claim 1. <5> The polymerizable compound (B) includes a polymerizable compound having one or more (meth)acryloyl groups in the molecule. <1> ~ <4> 13. The laminate according to claim 12 . <6> The electron beam curable resin composition further contains a pigment. <1> ~ <5> 13. The laminate according to claim 12 . <7> The surface layer, the first base material, the first adhesive layer, the second base material, the second adhesive layer, and the sealant layer are provided in this order; The second substrate comprises a stretched substrate made of a resin composition mainly composed of polypropylene. <1> ~ <6> 13. The laminate according to claim 12 . <8> The second substrate further comprises an inorganic oxide layer. <7> The laminate according to claim 1. <9> The first substrate further comprises an inorganic oxide layer. <1> ~ <8> 13. The laminate according to claim 12 . <10> The thickness of the surface layer is 3 μm or more and 35 μm or less. <1> ~ <9> 13. The laminate according to claim 12 . <11> The first substrate is in contact with the first adhesive layer. <1> ~ <10> 13. The laminate according to claim 12 . <12> <1> ~ <11> A packaging bag comprising the laminate described in any one of the above. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a laminate having excellent recyclability and excellent heat resistance and adhesion of a surface layer provided on the outermost surface. Also, according to the present disclosure, it is possible to provide a packaging bag including the laminate. [Brief description of the drawings]
[0013] [Figure 1] 1 is a cross-sectional schematic diagram showing one embodiment of a laminate of the present disclosure. [Diagram 2] 1 is a cross-sectional schematic diagram showing one embodiment of a laminate of the present disclosure. [Diagram 3] FIG. 1 is a perspective view illustrating one embodiment of a packaging bag produced using a laminate of the present disclosure. [Figure 4] FIG. 1 is a perspective view illustrating one embodiment of a packaging bag produced using a laminate of the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram showing a method for measuring laminate strength. [Figure 6] FIG. 13 is a diagram showing the measurement results of laminate strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The contents of the present disclosure will be described in detail below. In this specification, "(meth)acrylate" refers to acrylate and methacrylate, "(meth)acryl" refers to acryl and methacryl, and "(meth)acryloyl" refers to acryloyl and methacryloyl. In addition, in this specification, the "main component" of a layer or substrate refers to a component whose content in the layer or substrate is more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0015] (Laminate) 1, a laminate 10, which is one embodiment of the laminate of the present disclosure, includes at least a surface layer 11, a first substrate 12, a first adhesive layer 13, and a sealant layer 14. The surface layer 11 is located on the outer side of the laminate 10, and the sealant layer 14 is located on the inner side of the laminate 10. 2, a laminate 20, which is one embodiment of the laminate of the present disclosure, includes at least a surface layer 11, a first substrate 12, a first adhesive layer 13, a second substrate 15, a second adhesive layer 16, and a sealant layer 14. The surface layer 11 is located on the outer side of the laminate 20, and the sealant layer 14 is located on the inner side of the laminate 20. In the present disclosure, the first substrate includes a stretched substrate made of a resin composition mainly composed of polypropylene, and the sealant layer is made of a resin composition mainly composed of polypropylene. That is, the stretched substrate and the sealant layer of the first substrate are made of the same main component. This can improve the recyclability of the laminate of the present disclosure.
[0016] The polypropylene content in the entire laminate of the present disclosure is preferably 90% by mass or more, which can further improve the recyclability of the laminate of the present disclosure.
[0017] Each layer constituting the laminate of the present disclosure will be described below.
[0018] (1st base material) The first substrate of the laminate of the present disclosure includes a stretched substrate made of a resin composition mainly composed of polypropylene. The stretched polypropylene substrate as the first substrate is made of a resin composition mainly composed of polypropylene. In the following description, the stretched substrate containing the resin composition mainly composed of polypropylene is also referred to as "stretched polypropylene substrate".
[0019] The polypropylene may be any one of homopolypropylene, random polypropylene and block polypropylene, or may be a mixture of two or more selected from these. As the polypropylene, biomass-derived polypropylene and / or recycled polypropylene may be used. Homopolypropylene is a polymer of only propylene. Random polypropylene is a random copolymer of propylene and an α-olefin other than propylene. Block polypropylene is a polypropylene having a polymer block of propylene and a polymer block of at least an α-olefin other than propylene. The polymer block of at least an α-olefin other than propylene may be a polymer block of propylene and an α-olefin other than propylene.
[0020] Examples of the α-olefin include α-olefins having 2 to 20 carbon atoms other than propylene, specifically, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene.
[0021] Among polypropylenes, random polypropylene is preferred from the viewpoint of transparency, homopolypropylene is preferred when the rigidity and heat resistance of the packaging bag are important, and block polypropylene is preferred when the impact resistance of the packaging bag is important. In the present disclosure, among these polypropylenes, homopolypropylene and block polypropylene are more preferred from the viewpoints of heat resistance, impact resistance, and ease of opening, and homopolypropylene (propylene homopolymer) is even more preferred.
[0022] From the viewpoint of film-forming property and processability, the melt flow rate (MFR) of polypropylene is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and also preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, for example, 0.1 g / 10 min or more and 50 g / 10 min or less. The MFR of polypropylene is measured in accordance with JIS K7210-1:2014, Method A, under conditions of a temperature of 230° C. and a load of 2.16 kg.
[0023] The polypropylene content in the polypropylene oriented base material is preferably greater than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.
[0024] The stretched polypropylene substrate may contain a resin material other than polypropylene, such as a polyolefin other than polypropylene, such as polyethylene, an acrylic resin, a vinyl resin, a cellulose resin, a polyamide, a polyester, or an ionomer resin. The stretched polypropylene substrate may contain additives, such as crosslinkers, antioxidants, antiblocking agents, lubricants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0025] The stretched polypropylene substrate is one that has been subjected to a stretching treatment. A laminate including the stretched polypropylene substrate is excellent in, for example, heat resistance, impact resistance, water resistance, and dimensional stability, and is suitable as a laminate constituting a packaging bag that is to be subjected to, for example, a retort treatment or a boiling treatment. The stretching process may be uniaxial stretching or biaxial stretching. When stretching in the machine direction (flow direction of the substrate, MD direction), the stretching ratio is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. When stretching in the width direction (direction perpendicular to the MD direction, TD direction), the stretching ratio is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the substrate can be improved, and the printability of the substrate can be improved. From the viewpoint of the breaking limit of the substrate, the stretching ratio is preferably 15 times or less. The oriented polypropylene substrate used as the first substrate is, for example, a biaxially oriented polypropylene substrate.
[0026] The stretched polypropylene substrate may be surface-treated, which can improve the adhesion between the stretched polypropylene substrate and other layers, for example. Examples of surface treatment methods include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals. An easy-adhesion layer may be provided on the surface of the stretched polypropylene substrate.
[0027] The oriented polypropylene substrate may have a single layer structure or a multi-layer structure. The thickness of the stretched polypropylene substrate is preferably 10 μm or more, more preferably 15 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less. A laminate having a stretched substrate with a certain thickness or more has, for example, excellent strength and heat resistance. A laminate having a stretched substrate with a certain thickness or less has, for example, excellent processability.
[0028] (Second base material) The laminate of the present disclosure may include a second substrate. By including a second substrate in addition to a first substrate, the strength of the laminate can be further improved.
[0029] The second substrate comprises a polypropylene oriented substrate, similar to the first substrate. The polypropylene oriented substrate of the second substrate is also composed of a resin composition mainly composed of polypropylene, and is composed of the same main component as the polypropylene oriented substrate of the first substrate and the sealant layer described later. By adopting such a configuration, the recyclability of the laminate can be improved. The characteristics of the oriented polypropylene substrate included in the second substrate are similar to those of the oriented polypropylene substrate included in the first substrate, and therefore description thereof will be omitted here.
[0030] The thickness of the second base material is preferably 5 μm or more and 300 μm or less, and more preferably 7 μm or more and 100 μm or less. By making the thickness of the second base material equal to or greater than a certain level, the strength of the laminate can be improved, while by making the thickness of the second base material equal to or less than a certain level, the processability of the laminate can be improved.
[0031] The oriented polypropylene substrate of the first substrate and the oriented polypropylene substrate of the second substrate may be the same or different. For example, the oriented polypropylene substrate of the first substrate may be a biaxially oriented polypropylene substrate, and the oriented polypropylene substrate of the second substrate may be a uniaxially oriented polypropylene substrate.
[0032] (Inorganic oxide layer) At least one selected from the group consisting of the first substrate and the second substrate may have an inorganic oxide layer. The inorganic oxide layer contains one or more inorganic oxides, and is, for example, a vapor-deposited film of an inorganic oxide. When a substrate having an inorganic oxide layer is present in the laminate, the laminate has excellent gas barrier properties, specifically, oxygen barrier properties and water vapor barrier properties. A packaging bag made using such a laminate can suppress oxidation deterioration of the contents filled in the packaging bag and suppress weight loss of the contents.
[0033] Examples of inorganic oxides include aluminum oxide (alumina), silicon oxide (silica), magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, barium oxide, and silicon carbide oxide (carbon-containing silicon oxide). Among these, silica, silicon carbide oxide, and alumina are preferred.
[0034] In one embodiment, the inorganic oxide is more preferably silica since no aging treatment is required after the formation of the inorganic oxide layer.In one embodiment, the inorganic oxide is more preferably carbon-containing silicon oxide since the deterioration of the gas barrier property can be suppressed even when the laminate is bent.
[0035] The thickness of the inorganic oxide layer is preferably 1 nm or more, more preferably 5 nm or more, even more preferably 10 nm or more, and is preferably 150 nm or less, more preferably 60 nm or less, even more preferably 40 nm or less, for example, 1 nm or more and 150 nm or less. A laminate having an inorganic oxide layer with a certain thickness or more has excellent oxygen barrier properties and water vapor barrier properties, for example. A laminate having an inorganic oxide layer with a certain thickness or less can suppress the occurrence of cracks in the inorganic oxide layer and has excellent recyclability, for example.
[0036] The surface of the inorganic oxide layer may be subjected to the above-mentioned surface treatment.
[0037] Examples of methods for forming an inorganic oxide layer, particularly an inorganic oxide vapor deposition film, include physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.
[0038] The inorganic oxide layer may be a single layer formed by one deposition process, or may be a multilayer formed by multiple deposition processes. When the inorganic oxide layer is a multilayer, each layer may be composed of the same inorganic oxide or different inorganic oxides. Each layer may be formed by the same method or different methods.
[0039] The inorganic oxide layer is preferably a vapor-deposited film formed by a CVD method, and more preferably a carbon-containing silicon oxide vapor-deposited film formed by a CVD method. A laminate including such an inorganic oxide layer has, for example, excellent bending resistance.
[0040] The carbon-containing silicon oxide vapor deposition film contains silicon, oxygen and carbon. In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the carbon ratio C is preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and is preferably 50% or less, more preferably 40% or less, even more preferably 35% or less, for example, 3% or more and 50% or less, relative to 100% in total of the three elements silicon, oxygen, and carbon. By setting the carbon ratio C in the above range, for example, even if the laminate is bent, the deterioration of the gas barrier property can be suppressed. In this specification, the ratio of each element is on a molar basis.
[0041] In one embodiment of the carbon-containing silicon oxide vapor deposition film, the silicon ratio Si is preferably 1% or more, more preferably 3% or more, and even more preferably 8% or more, and is preferably 45% or less, more preferably 38% or less, and even more preferably 33% or less, for example, 1% or more and 45% or less, relative to the total of the three elements silicon, oxygen, and carbon (100%). The oxygen ratio O is preferably 10% or more, more preferably 20% or more, and even more preferably 25% or more, and is preferably 70% or less, more preferably 65% or less, and even more preferably 60% or less, for example, 10% or more and 70% or less, relative to the total of the three elements silicon, oxygen, and carbon (100%). By setting the silicon ratio Si and the oxygen ratio O in the above ranges, for example, even if the laminate is bent, the deterioration of the gas barrier property can be further suppressed.
[0042] In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the oxygen ratio O is preferably higher than the carbon ratio C, and the silicon ratio Si is preferably lower than the carbon ratio C. The oxygen ratio O is preferably higher than the silicon ratio Si. That is, the ratios are preferably in the order of O, C, and Si. This makes it possible to further suppress the deterioration of the gas barrier properties even when the laminate is bent, for example.
[0043] The proportions C, Si, and O in the carbon-containing silicon oxide vapor-deposited film are measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the following measurement conditions.
[0044] (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (non-monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) Measurement area: approx. 6mmφ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Ar gas introduction pressure: 2.0×10 -2 Pa Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Ion sputtering time: 30 seconds, spectrum collected
[0045] (covering layer) At least one selected from the group consisting of the first substrate and the second substrate may further include a coating layer on the inorganic oxide layer. That is, at least one selected from the group consisting of the first substrate and the second substrate may further include a coating layer on the surface of the inorganic oxide layer opposite to the surface facing the stretched polypropylene substrate. The presence of a substrate having a coating layer in the laminate provides the laminate with excellent oxygen barrier properties and water vapor barrier properties, for example. When at least one selected from the group consisting of the first substrate and the second substrate has a coating layer, the coating layer may be adjacent to the first adhesive layer or the second adhesive layer.
[0046] In one embodiment, the coating layer contains a resin component. Examples of the resin component include polyolefins such as polyethylene, polypropylene, polybutene, and polymethylpentene, vinyl resins, acrylic resins, polyesters, urethane resins, melamine resins, and epoxy resins. The content of the resin component in the coating layer is preferably more than 50% by mass, more preferably 75% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, for example, more than 50% by mass and 95% by mass or less. The coating layer may contain the above-mentioned additives.
[0047] The thickness of the coating layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 1 μm or less, for example, 0.01 μm or more and 5 μm or less. Such a coating layer has, for example, excellent scratch resistance.
[0048] The coating layer can be formed, for example, by applying a coating liquid for the coating layer to the surface of the inorganic oxide layer and drying it. The coating liquid for the coating layer can be prepared, for example, by mixing the above-mentioned resin component and, if necessary, an additive and a solvent. Details of these components are as described above. Examples of the method for applying the coating liquid for the coating layer include known coating methods. Examples of the method for drying the applied coating liquid for the coating layer include methods that apply heat such as hot air drying, hot roll drying, and infrared irradiation. The drying temperature may be 50°C or higher, or 150°C or lower.
[0049] In one embodiment, the coating layer may be a barrier coat layer containing a gas barrier resin. Examples of the gas barrier resin include ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyacrylonitrile, polyester, polyamide such as nylon 6, nylon 6,6, and polymetaxylylene adipamide, polyurethane, and acrylic resin. The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. Such a barrier coat layer has, for example, excellent gas barrier properties. The barrier coat layer may contain the above-mentioned additives.
[0050] The thickness of the barrier coat layer containing the gas barrier resin is preferably 0.01 μm or more, more preferably 0.1 μm or more, and also preferably 10 μm or less, more preferably 5 μm or less, for example, 0.01 μm or more and 10 μm or less. By providing a barrier coat layer having a certain thickness or more, the laminate has excellent gas barrier properties. By providing a barrier coat layer having a certain thickness or less, the processability and recyclability of the laminate can be improved.
[0051] The barrier coat layer can be formed, for example, by dissolving or dispersing a material such as a gas barrier resin in water or an appropriate organic solvent, applying the resulting coating liquid to the surface of the inorganic oxide layer, and drying it. The barrier coat layer can also be formed, for example, by applying a commercially available barrier coating agent and drying it.
[0052] In one embodiment, the coating layer may be a gas barrier coating film formed by polycondensing a composition containing a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, and the like. By providing a gas barrier coating film on the inorganic oxide layer, the laminate has excellent gas barrier properties. The gas barrier coating film contains a hydrolysis polycondensate obtained by hydrolyzing and polycondensing the metal alkoxide and the like by a sol-gel method. By providing such a gas barrier coating film on the inorganic oxide layer, for example, the occurrence of cracks in the inorganic oxide layer can be effectively suppressed.
[0053] The metal alkoxide is represented, for example, by the formula (1). R 1 n M(OR 2 ) m (1) In formula (1), R 1 and R 2 each independently represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. 1 and R 2 In the above, examples of the organic group include alkyl groups having 1 to 8 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-hexyl, and n-octyl. The metal atom M is, for example, silicon, zirconium, titanium, or aluminum. Examples of the metal alkoxide include alkoxysilanes, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.
[0054] Examples of the water-soluble polymer include hydroxyl group-containing polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Either polyvinyl alcohol or ethylene-vinyl alcohol copolymer may be used, or both may be used in combination, depending on the desired physical properties such as oxygen barrier property, water vapor barrier property, water resistance, and weather resistance. Also, a gas barrier coating film obtained using polyvinyl alcohol and a gas barrier coating film obtained using an ethylene-vinyl alcohol copolymer may be laminated. The amount of the water-soluble polymer used is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and preferably 500 parts by mass or less, based on 100 parts by mass of the metal alkoxide.
[0055] A silane coupling agent may be used together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used, and an organoalkoxysilane having an epoxy group is preferred, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The amount of the silane coupling agent used is preferably 1 part by mass or more and 20 parts by mass or less relative to 100 parts by mass of the metal alkoxide.
[0056] The gas barrier composition may contain water in an amount of preferably 0.1 mol or more, more preferably 0.5 mol or more, and preferably 100 mol or less, more preferably 60 mol or less, per mol of metal alkoxide. By making the water content at a certain level or more, for example, the oxygen barrier property and water vapor barrier property of the laminate can be improved. By making the water content at a certain level or less, for example, the hydrolysis reaction can be carried out quickly.
[0057] The gas barrier composition may contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butyl alcohol.
[0058] The sol-gel catalyst is preferably an acid or an amine compound. Examples of the acid include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid; and organic acids such as acetic acid, tartaric acid, etc. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less per 1 mol of the total molar amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent.
[0059] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is suitable, such as N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. The amount of the amine compound used is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and is preferably 1.0 parts by mass or less, more preferably 0.3 parts by mass or less, based on 100 parts by mass of the total amount of the metal alkoxide and the silane coupling agent.
[0060] Examples of methods for applying the gas barrier composition include application means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, and applicator coating.
[0061] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. A gas barrier composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent. A polycondensation reaction gradually proceeds in the composition. The composition is applied on an inorganic oxide layer by a conventional method and dried. This drying causes further polycondensation of the metal alkoxide and the water-soluble polymer (and the silane coupling agent when the composition contains a silane coupling agent) to form a composite polymer layer. The above operation may be repeated to laminate a plurality of composite polymer layers. For example, the applied composition is heated at a temperature of preferably 20° C. or higher, more preferably 50° C. or higher, and even more preferably 70° C. or higher, and also at a temperature of preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower for 1 second to 10 minutes. This allows the formation of a gas barrier coating film.
[0062] The thickness of the gas barrier coating film is preferably 0.01 μm or more, more preferably 0.1 μm or more, and is preferably 2 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less, for example, 0.01 μm or more and 2 μm or less, which can improve the gas barrier property, suppress the occurrence of cracks in the inorganic oxide layer, and improve the recyclability of the packaging bag.
[0063] (Surface layer) The surface layer of the laminate of the present disclosure is provided on the surface of the above-mentioned first substrate (the outer surface of the first substrate) and is composed of a cured product of an electron beam curable resin composition. The electron beam curable resin composition contains a polymerization initiator (A) and a polymerizable compound (B), and the polymerization initiator (A) is a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more. By curing such an electron beam curable resin composition to form a surface layer, migration due to heat can be suppressed and the heat resistance of the surface layer can be improved. The reason why such an effect is achieved is considered to be as follows. The electron beam curable resin composition contains, as the polymerization initiator (A), a hydrogen abstraction type polymerization initiator having a molecular weight of not less than 500. This inhibits the generation of low molecular weight components such as decomposition products of the polymerization initiator due to heat in the surface layer, and also inhibits migration. As a result, it is believed that the physical properties of the surface layer are less likely to change even when exposed to high temperatures, and the heat resistance of the surface layer is improved.
[0064] In addition, the electron beam curable resin composition has a relatively low content of polymerization initiator and a relatively high content of polymerizable compound compared to ultraviolet-curable resin compositions (ultraviolet-curable inks) that have been used in conventional inkjet printing. When an electron beam curable resin composition containing a large amount of polymerizable compound is cured, a cured product with a high crosslink density is obtained, and the thermal shrinkage of the substrate to which the cured product is in close contact is suppressed. In other words, the surface layer formed of the cured product of the electron beam curable resin composition also contributes to improving the heat resistance of the substrate in that it can suppress the thermal shrinkage of the substrate.
[0065] The content of the polymerization initiator (A) in the electron beam curable resin composition (i.e., the total content of the polymerization initiators contained in the electron beam curable resin composition) is preferably 2 mass% or less, which suppresses an increase in viscosity of the electron beam curable resin composition and suppresses a decrease in dischargeability (specifically, dischargeability from a jet head of the electron beam curable resin composition; the same applies below) caused by the increase in viscosity of the electron beam curable resin composition.
[0066] Hereinafter, each component that may be contained in the electron beam curable resin composition will be described.
[0067] <Polymerization initiator (A)> The electron beam curable resin composition contains a polymerization initiator (A). The content of the polymerization initiator (A) is preferably more than 0 mass % and 2 mass % or less based on the total amount of the electron beam curable resin composition. Here, the polymerization initiator (A) means all polymerization initiators that can be contained in the electron beam curable resin composition, and the content of the polymerization initiator (A) means the total content of all polymerization initiators that can be contained in the electron beam curable resin composition.
[0068] When the content of the polymerization initiator (A) is more than 0% by mass, the curability of the electron beam curable resin composition against irradiation with an electron beam (i.e., the polymerizability of the polymerizable compound (B)) is ensured. When the electron beam curable resin composition is cured by irradiation with an electron beam, the content of the polymerization initiator (A) can be smaller than when the electron beam curable resin composition is cured by irradiation with an ultraviolet ray. From the viewpoint of further improving the curability of the electron beam curable resin composition against irradiation with an electron beam, the content of the polymerization initiator (A) is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.6% by mass or more. On the other hand, when the content of the polymerization initiator (A) is 2% by mass or less, migration is suppressed. From the viewpoint of further suppressing migration, the content of the polymerization initiator (A) is preferably 1.5% by mass or less.
[0069] An example of a preferred range for the content of the polymerization initiator (A) is 0.1% by mass or more and 2% by mass or less.
[0070] The polymerization initiator (A) includes a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more. In the case of a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, the molecular weight of 500 or more contributes to the effect of suppressing migration. In the case of a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, the fact that it is a hydrogen abstraction type contributes to curing properties with respect to irradiation with an electron beam.
[0071] The preferred range of the content of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more relative to the total amount of the electron beam curable resin composition is the same as the preferred range of the content of the polymerization initiator (A) relative to the total amount of the electron beam curable resin composition. However, the polymerization initiator (A) in the electron beam curable resin composition may consist solely of a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, or may contain a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more and another polymerization initiator. Therefore, the content (% by mass) of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more relative to the total amount of the electron beam curable resin composition does not need to be the same as the content (% by mass) of the polymerization initiator (A) relative to the total amount of the electron beam curable resin composition.
[0072] An example of a preferred range for the content of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more is 0.1% by mass or more and 2% by mass or less.
[0073] The proportion of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more in the polymerization initiator (A) is preferably 50 mass % or more, more preferably 60 mass % or more, even more preferably 80 mass % or more, and is preferably 100 mass % or less. The proportion of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more in the polymerization initiator (A) may be 100 mass %. In other words, the polymerization initiator (A) does not need to contain any polymerization initiator other than the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more.
[0074] The content of the polymerization initiator other than the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more is preferably 0.1 mass % or less based on the total amount of the electron beam curable resin composition.
[0075] The molecular weight of a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more is preferably 700 or more, more preferably 800 or more, and further preferably 1,000 or more. The upper limit of the molecular weight of the hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more is preferably 5,000, more preferably 4,000, and further preferably 3,000.
[0076] The hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more preferably includes a hydrogen abstraction type polymerization initiator having a molecular weight of 1,000 or more. In this case, a hydrogen abstraction type polymerization initiator having a molecular weight of 1,000 or more and a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more and less than 100 may be used in combination. The proportion of hydrogen abstraction type polymerization initiators having a molecular weight of 1,000 or more in the hydrogen abstraction type polymerization initiators having a molecular weight of 500 or more is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and is preferably 100% by mass or less.
[0077] The hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more is preferably at least one of a thioxanthone compound and a benzophenone compound.
[0078] As a thioxanthone compound serving as a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, a compound represented by the following formula (S1) can be mentioned. Benzophenone compounds serving as hydrogen abstraction polymerization initiators having a molecular weight of 500 or more include compounds represented by the following formula (S2).
[0079] [ka]
[0080] In formula (S1) and formula (S2), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group having 1 to 5 carbon atoms or a halogen atom; x and y each independently represent an integer of 2 to 4; j and m each independently represent an integer of 0 to 4; k and n each independently represent an integer of 0 to 3; and when j, k, m, and n are integers of 2 or more, a plurality of R 1 , R 2 , R 3 and R 4 may be the same or different, and X 1 represents an x-valent linking group containing at least one of a hydrocarbon chain, an ether bond, and an ester bond, 2represents a y-valent linking group containing at least one of a hydrocarbon chain, an ether bond, and an ester bond.
[0081] As for preferred embodiments and specific examples of the compound represented by formula (S1), reference may be made to the descriptions in paragraphs 0035 to 0053 of JP-A No. 2014-162828.
[0082] As the compound represented by formula (S1), a commercially available compound can also be used. in particular, Speedcure (registered trademark) manufactured by Lambson 7010(1,3-di({α-[1-chloro-9-oxo-9H-thioxanthen-4-yl]oxy}acetylpoly[oxy(1-methylethylene)]oxy)-2,2-bis({α-[1-chloro-9-oxo-9H-thioxanthen-4-yl]oxy}acetylpoly[oxy(1-methylethylene)]oxymethyl)propane, CAS No. 1003567-83-6); OMNIPOL® TX (Polybutyleneglycol bis(9-oxo-9H-thioxanthenyloxy)acetate, CAS No. 813452-37-8) from IGM Resins BV; Genopo TX-2 manufactured by RanA.G.; etc. are examples.
[0083] As for preferred embodiments and specific examples of the compound represented by formula (S2), reference may be made to the descriptions in paragraphs 0054 to 0075 of JP-A No. 2014-162828.
[0084] As the compound represented by formula (S2), a commercially available compound can also be used. A specific example is OMNIPOL BP (Polybutyleneglycol bis(4-benzoylphenoxy)acetate, CAS No. 515136-48-8) manufactured by IGM Resins BV.
[0085] <Polymerizable compound (B)> The electron beam curable resin composition contains a polymerizable compound (B). Here, the polymerizable compound (B) means all polymerizable compounds that can be contained in the electron beam curable resin composition, and may be one type of polymerizable compound or two or more types of polymerizable compounds.
[0086] The polymerizable compound is not particularly limited as long as it is a compound containing a polymerizable group in the molecule. The polymerizable group is preferably an ethylenically unsaturated group. The ethylenically unsaturated group is preferably a (meth)acryloyl group, a vinyl group, an allyl group, or a styryl group, and more preferably a (meth)acryloyl group or a vinyl group.
[0087] The molecular weight of the polymerizable compound is not particularly limited, but is preferably 5,000 or less, more preferably 2,000 or less, further preferably 1,500 or less, and particularly preferably 1,000 or less. The lower limit of the molecular weight of the polymerizable compound is, for example, 58 (the molecular weight of methyl vinyl ether).
[0088] The polymerizable compound (B) may be a monofunctional polymerizable compound (i.e., a compound containing only one polymerizable group), a polyfunctional polymerizable compound (i.e., a compound containing two or more polymerizable groups), or both a monofunctional polymerizable compound and a polyfunctional polymerizable compound. As the polyfunctional polymerizable compound, from the viewpoint of reducing the viscosity and improving the dischargeability of the electron beam curable resin composition, a bifunctional polymerizable compound (i.e., a compound containing two polymerizable groups) or a trifunctional polymerizable compound (i.e., a compound containing three polymerizable groups) is preferred, and a bifunctional polymerizable compound is more preferred. The polymerizable compound (B) preferably contains at least one of a monofunctional polymerizable compound and a bifunctional polymerizable compound, and more preferably contains both a monofunctional polymerizable compound and a bifunctional polymerizable compound. When the polymerizable compound (B) contains at least one of a monofunctional polymerizable compound and a bifunctional polymerizable compound, the total proportion of the monofunctional polymerizable compound and the bifunctional polymerizable compound in the total amount of the electron beam curable resin composition is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 80 mass% or more.
[0089] In the electron beam curable resin composition, the polymerizable compound (B) preferably contains a monofunctional polymerizable compound and a polyfunctional polymerizable compound (preferably a difunctional polymerizable compound). In this case, the content mass ratio of the monofunctional polymerizable compound to the polyfunctional polymerizable compound (hereinafter also referred to as the "monofunctional / polyfunctional ratio" or "monofunctional / polyfunctional") is preferably 0.2 or more, more preferably 0.4 or more, and is preferably 2.5 or less, more preferably 2.3 or less. When the monofunctional / polyfunctional ratio is equal to or greater than a certain level, the image quality and / or adhesion are further improved. When the monofunctional / polyfunctional ratio is equal to or lower than a certain level, migration is further suppressed.
[0090] Specific examples of the polymerizable compound (B) are shown below, but the polymerizable compound (B) is not limited to the following specific examples.
[0091] -Monofunctional polymerizable compound- Examples of the monofunctional polymerizable compound include monofunctional (meth)acrylates, monofunctional (meth)acrylamides, monofunctional aromatic vinyl compounds, monofunctional vinyl ethers, and monofunctional N-vinyl compounds.
[0092] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tert-octyl (meth)acrylate, isoamyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and cyclohexyl (meth)acrylate. , 4-n-butylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, bornyl (meth)acrylate, norbornyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, 2-ethylhexyl diglycol (meth)acrylate, butoxyethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 4-bromobutyl (meth)acrylate, cyanoethyl (meth)acrylate, benzyl (meth)acrylate, butoxymethyl (meth)acrylate acrylate, 3-methoxybutyl (meth)acrylate, 2-(2-methoxyethoxy)ethyl (meth)acrylate, 2-(2-butoxyethoxy)ethyl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-tetrafluoroethyl (meth)acrylate, 1H,1H,2H,2H-perfluorodecyl (meth)acrylate, 4-butylphenyl (meth)acrylate, phenyl (meth)acrylate, 2,4,5-tetramethylphenyl (meth)acrylate, 4-chlorophenyl (meth)acrylate, 2-phenoxy Dimethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, glycidyl (meth)acrylate, glycidyloxybutyl (meth)acrylate, glycidyloxyethyl (meth)acrylate, glycidyloxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate,4-Hydroxybutyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, phenyl glycidyl ether (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, trimethoxysilylpropyl (meth)acrylate, trimethylsilylpropyl (meth)acrylate, polyethylene oxide monomethyl ether (meth)acrylate, polyethylene oxide (meth)acrylate, polyethylene oxide monoalkyl ether (meth)acrylate, dipropylene glycol (meth)acrylate, polypropylene oxide monoalkyl ether (meth)acrylate, 2-methacryloyloxyethyl succinate, 2-methacryloyloxyhexahydrophthalic acid, 2-methacryloyloxyethyl succinate Examples of the methacrylate include diethyl-2-hydroxypropyl phthalate, butoxydiethylene glycol (meth)acrylate, trifluoroethyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene oxide-modified (hereinafter referred to as EO-modified) phenol (meth)acrylate, EO-modified cresol (meth)acrylate, EO-modified nonylphenol (meth)acrylate, propylene oxide-modified (hereinafter referred to as PO-modified) nonylphenol (meth)acrylate, EO-modified 2-ethylhexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, (3-ethyl-3-oxetanylmethyl) (meth)acrylate, and phenoxyethylene glycol (meth)acrylate.
[0093] Examples of monofunctional (meth)acrylamides include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, Nn-butyl(meth)acrylamide, Nt-butyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methylol(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and (meth)acryloylmorpholine.
[0094] Examples of monofunctional aromatic vinyl compounds include styrene, dimethylstyrene, trimethylstyrene, isopropylstyrene, chloromethylstyrene, methoxystyrene, acetoxystyrene, chlorostyrene, dichlorostyrene, bromostyrene, vinyl benzoic acid methyl ester, 3-methylstyrene, 4-methylstyrene, 3-ethylstyrene, 4-ethylstyrene, 3-propylstyrene, 4-propylstyrene, 3-butylstyrene, 4-butylstyrene, 3-hexylstyrene, 4-hexylstyrene, 3-octylstyrene, 4-octylstyrene, 3-(2-ethylhexyl)styrene, 4-(2-ethylhexyl)styrene, allylstyrene, isopropenylstyrene, butenylstyrene, octenylstyrene, 4-t-butoxycarbonylstyrene, and 4-t-butoxystyrene.
[0095] Examples of monofunctional vinyl ethers include methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, n-butyl vinyl ether, t-butyl vinyl ether, 2-ethylhexyl vinyl ether, n-nonyl vinyl ether, lauryl vinyl ether, cyclohexyl vinyl ether, cyclohexylmethyl vinyl ether, 4-methylcyclohexylmethyl vinyl ether, benzyl vinyl ether, dicyclopentenyl vinyl ether, 2-dicyclopentenoxyethyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, butoxyethyl vinyl ether, methoxyethoxyethyl vinyl ether, ethoxyethoxyethyl vinyl ether, methoxypolyethylene glycol vinyl ether, tetrahydrofurfuryl vinyl ether, 2-hydroxyethyl vinyl ether, 2-hydroxypropyl vinyl ether, 4-hydroxybutyl vinyl ether, 4-hydroxymethylcyclohexylmethyl vinyl ether, diethylene glycol monovinyl ether, polyethylene glycol vinyl ether, chloroethyl vinyl ether, chlorobutyl vinyl ether, chloroethoxyethyl vinyl ether, phenylethyl vinyl ether, and phenoxypolyethylene glycol vinyl ether.
[0096] Examples of the monofunctional N-vinyl compound include N-vinylcaprolactam, N-vinylpyrrolidone, N-vinyloxazolidinone, and N-vinyl-5-methyloxazolidinone.
[0097] The monofunctional polymerizable compound preferably contains at least one of a monofunctional (meth)acrylate and a monofunctional N-vinyl compound, and more preferably contains at least one of a monofunctional (meth)acrylate containing an alicyclic structure and a monofunctional N-vinyl compound. The monofunctional (meth)acrylate containing an alicyclic structure is preferably isobornyl (meth)acrylate, norbornyl (meth)acrylate, or adamantyl (meth)acrylate, and more preferably isobornyl (meth)acrylate. The total proportion of the monofunctional (meth)acrylate (preferably a monofunctional (meth)acrylate containing an alicyclic structure) and the monofunctional N-vinyl compound in the monofunctional polymerizable compound is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 80 mass% or more, and preferably 100 mass% or less. The proportion of the monofunctional N-vinyl compound in the monofunctional polymerizable compound is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more.
[0098] -Bifunctional polymerizable compound- Examples of the difunctional polymerizable compound include difunctional (meth)acrylates, difunctional vinyl ethers, and difunctional monomers containing a vinyl ether group and a (meth)acryloyl group.
[0099] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, hexanediol di(meth)acrylate, and heptanediol di(meth)acrylate. , EO-modified neopentyl glycol di(meth)acrylate, PO-modified neopentyl glycol di(meth)acrylate, EO-modified hexanediol di(meth)acrylate, PO-modified hexanediol di(meth)acrylate, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, dodecanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, and the like.
[0100] Examples of bifunctional vinyl ethers include 1,4-butanediol divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, butylene glycol divinyl ether, hexanediol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, bisphenol A alkylene oxide divinyl ether, and bisphenol F alkylene oxide divinyl ether.
[0101] An example of a bifunctional polymerizable compound containing a vinyl ether group and a (meth)acryloyl group is 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0102] - Polymerizable compounds with three or more functional groups - Examples of tri- or higher functional polymerizable compounds include tri- or higher functional (meth)acrylates, tri- or higher functional vinyl ethers, and the like.
[0103] Examples of the trifunctional or higher (meth)acrylate include trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerin polyglycidyl ether poly(meth)acrylate, and tris(2-acryloyloxyethyl)isocyanurate.
[0104] Examples of trifunctional or higher vinyl ethers include trimethylolethane trivinyl ether, trimethylolpropane trivinyl ether, ditrimethylolpropane tetravinyl ether, glycerin trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, dipentaerythritol hexavinyl ether, EO-modified trimethylolpropane trivinyl ether, PO-modified trimethylolpropane trivinyl ether, EO-modified ditrimethylolpropane tetravinyl ether, PO-modified ditrimethylolpropane tetravinyl ether, EO-modified pentaerythritol tetravinyl ether, PO-modified pentaerythritol tetravinyl ether, EO-modified dipentaerythritol hexavinyl ether, and PO-modified dipentaerythritol hexavinyl ether.
[0105] -Urethane (meth)acrylate- The above-mentioned difunctional polymerizable compounds and trifunctional or higher polymerizable compounds also include urethane (meth)acrylates. The urethane (meth)acrylate may be a reaction product of a difunctional isocyanate compound and a hydroxyl group-containing (meth)acrylate. Examples of the bifunctional isocyanate compound include: Aliphatic diisocyanates such as methylene diisocyanate, dimethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dipropyl ether diisocyanate, 2,2-dimethylpentane diisocyanate, 3-methoxyhexane diisocyanate, octamethylene diisocyanate, 2,2,4-trimethylpentane diisocyanate, nonamethylene diisocyanate, decamethylene diisocyanate, 3-butoxyhexane diisocyanate, 1,4-butylene glycol dipropyl ether diisocyanate, and thiodihexyl diisocyanate; Aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, dimethylbenzene diisocyanate, ethylbenzene diisocyanate, isopropylbenzene diisocyanate, tolidine diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 2,7-naphthalene diisocyanate, metaxylylene diisocyanate, paraxylylene diisocyanate, and tetramethylxylylene diisocyanate; Alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate; etc. Examples of hydroxyl group-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, phenyl glycidyl ether (meth)acrylate, pentaerythritol (meth)triacrylate, and dipentaerythritol penta(meth)acrylate.
[0106] -Epoxy (meth)acrylate- The above-mentioned difunctional polymerizable compounds and trifunctional or higher polymerizable compounds also include epoxy (meth)acrylates. Here, epoxy (meth)acrylate means a reaction product of a carboxy group in (meth)acrylic acid and two or three epoxy groups in an epoxy compound containing two or three epoxy groups. Therefore, the structure of epoxy(meth)acrylate does not contain an epoxy group, and in this respect, epoxy(meth)acrylate differs from the epoxy compound, which is an example of the above-mentioned cationically polymerizable monomer.
[0107] Epoxy (meth)acrylates include reaction products of (meth)acrylic acid and epoxy resins. Examples of epoxy resins include bisphenol A type epoxy resins and cresol novolac type epoxy resins.
[0108] <Pigment (C)> The electron beam curable resin composition may contain a pigment (C). That is, the electron beam curable resin composition may be a transparent electron beam curable resin composition that does not contain the pigment (C). Here, the pigment (C) means all pigments that can be contained in the electron beam curable resin composition, and may be one type of pigment or two or more types of pigments.
[0109] The pigment can be contained in the electron beam curable resin composition as a pigment dispersion. The pigment dispersion is a liquid obtained by dispersing a pigment in a liquid medium using a dispersant, and contains at least a pigment, a dispersant, and a liquid medium. When a self-dispersing pigment is used as the pigment, it is not necessary to add a dispersant to the electron beam curable resin composition.
[0110] The liquid medium may be, for example, an organic solvent. The liquid medium may be the above-mentioned polymerizable compound contained in the electron beam curable resin composition.
[0111] The pigment may be any of organic and inorganic pigments that are commonly available on the market. The pigment may also be an invisible pigment having infrared absorbing properties.
[0112] The content of the pigment (C) (i.e., the total content of the pigment contained in the electron beam curable resin composition) is preferably 1 mass % or more, more preferably 2 mass % or more, and preferably 20 mass % or less, more preferably 10 mass % or less, based on the total amount of the electron beam curable resin composition.
[0113] <Dispersant> The electron beam curable resin composition may contain at least one dispersant for dispersing the pigment (C).
[0114] As the dispersant, any known dispersant can be used. From the viewpoint of dispersion stability, the dispersant is preferably a compound having both a hydrophilic structure and a hydrophobic structure.
[0115] Examples of dispersants include low molecular weight dispersants having a molecular weight of less than 1000, such as higher fatty acid salts, alkyl sulfates, alkyl ester sulfates, alkyl sulfonates, sulfosuccinates, naphthalene sulfonates, alkyl phosphates, polyoxyalkylene alkyl ether phosphates, polyoxyalkylene alkyl phenyl ethers, polyoxyethylene polyoxypropylene glycols, glycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene fatty acid amides, and amine oxides.
[0116] The dispersant may be a high molecular weight dispersant having a molecular weight of 1000 or more obtained by copolymerizing a hydrophilic monomer and a hydrophobic monomer. From the viewpoint of dispersion stability, the hydrophilic monomer is preferably a dissociable group-containing monomer, and is preferably a dissociable group-containing monomer having a dissociable group and an ethylenically unsaturated bond. Examples of the dissociable group-containing monomer include a carboxyl group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer. From the viewpoint of dispersion stability, the hydrophobic monomer is preferably an aromatic group-containing monomer having an aromatic group and an ethylenically unsaturated bond, or an aliphatic hydrocarbon group-containing monomer having an aliphatic hydrocarbon group and an ethylenically unsaturated bond. The polymer may be either a random copolymer or a block copolymer.
[0117] The dispersant may be a commercially available product. Examples of commercially available products include DISPERBYK-101, DISPERBYK-102, DISPERBYK-103, DISPERBYK-106, DISPERBYK-110, DISPERBYK-111, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-164, DISPERBYK-166, DISPERBYK-167, DISPERBYK-168, DISPERBYK-170, DISPERBYK-171, DISPERBYK-174, DISPERBYK-182 (manufactured by BYK Chemie); and SOLSPERSE3000, SOLSPERSE5000, SOLSPERSE9000, SOLSPERSE12000, SOLSPERSE13240, SOLSPERSE13940, SOLSPERSE17000, SOLSPERSE22000, SOLSPERSE24000, SOLSPERSE26000, SOLSPERSE28000, SOLSPERSE32000, SOLSPERSE36000, SOLSPERSE39000, SOLSPERSE41000, SOLSPERSE71000 (manufactured by Lubrizol) Examples include:
[0118] As a dispersing device for dispersing the pigment, a known dispersing device can be used, and examples thereof include a ball mill, a sand mill, a bead mill, a roll mill, a jet mill, a paint shaker, an attritor, an ultrasonic disperser, and a disperser.
[0119] In the electron beam curable resin composition, the ratio of the dispersant content to the pigment content (i.e., dispersant content / pigment content) is, from the viewpoint of dispersion stability, preferably 0.05 or more, more preferably 0.1 or more, and is preferably 1.0 or less, more preferably 0.8 or less, based on mass.
[0120] <Amine with molecular weight of 500 or more> The electron beam curable resin composition preferably further contains at least one amine having a molecular weight of 500 or more. This results in better image quality and better suppression of migration. In this case, the content of the amine having a molecular weight of 500 or more is preferably more than 0 mass % and 2 mass % or less based on the total amount of the electron beam curable resin composition. When the content of amines having a molecular weight of 500 or more is 2% by mass or less, migration is further suppressed. From the viewpoint of further suppressing migration, the content of amines having a molecular weight of 500 or more is preferably 1.5% by mass or less.
[0121] An example of a preferred range for the content of amines having a molecular weight of 500 or more is 0.1% by mass or more and 2% by mass or less.
[0122] The amine having a molecular weight of 500 or more is not particularly limited as long as it contains an amino group (that is, contains at least one of an unsubstituted amino group and a substituted amino group) and has a molecular weight of 500 or more. An example of the amine having a molecular weight of 500 or more is a compound represented by the following formula (X).
[0123] NR 1 R 2 R 3 … Formula (X) [In formula (X), R 1 , R 2 , and R 3 each independently represents a hydrogen atom or a substituent. 1 , R 2 , and R 3 is selected so that the molecular weight of the compound represented by formula (X) is 500 or more.
[0124] In formula (X), R 1 , R 2 , and R 3 It is preferred that two or more of R 1 , R 2 , and R 3 It is more preferable that all three of R are substituents. 1 , R 2 , and R 3However, it is also a preferred embodiment that the acryloyloxy group is contained.
[0125] An amine having a molecular weight of 500 or more contains at least one amino group. From the viewpoints of viscosity and suppression of migration, however, an amine having a molecular weight of 500 or more preferably contains 1 to 6 amino groups, more preferably 1 to 3 amino groups, and even more preferably 1 or 2 amino groups.
[0126] Furthermore, when the amine having a molecular weight of 500 or more contains a (meth)acryloyloxy group, from the viewpoints of reactivity and viscosity, the amine having a molecular weight of 500 or more preferably contains 1 to 6 (meth)acryloyl groups, more preferably 1 to 4 (meth)acryloyl groups, and even more preferably 1 or 2 (meth)acryloyl groups.
[0127] As the amine having a molecular weight of 500 or more, a commercially available product may be used. Commercially available amines with a molecular weight of 500 or more include, for example: GENOMER5161, GENOMER5271, GENOMER5275, GENOMER5795 (all from RAHN); CN371, CN373, CN383, CN384, CN386, CN501, CN550, CN551 (all from Sartomer); EBECRYL7100, EBECRYL80, EBECRYL81, EBECRYL83, EBECRYL84, EBECRYLP115 (all from Daicel-Cytec Co., Ltd.); Laromer PO77F (LR8946), Laromer LR8956, Laromer LR8996, Laromer PO94F (LR8894) (BASF); Photomer4771, Photomer4775, Photomer4967, Photomer5006, Photomer5096, Photomer5662, Photomer5930 (all from Cognis); DoublecureEPD, DoublecureOPD, Doublecure115, Doublecure225, Doublecure645, PolyQ222, PolyQ226, PolyQ224, PolyQ101 (all from DoubleBond Chemicals); Omnipol ASA (IGM); etc.
[0128] For amines having a molecular weight of 500 or more, reference can be made to, for example, paragraphs 0072 to 0074 of JP-A No. 2011-68783 and paragraphs 0069 to 0070 of JP-A No. 2015-160890.
[0129] From the viewpoint of further suppressing migration, the molecular weight of the amine having a molecular weight of 500 or more is preferably 700 or more, more preferably 800 or more, and further preferably 1000 or more. The upper limit of the molecular weight of the amine having a molecular weight of 500 or more is preferably 10,000, more preferably 7,000, and further preferably 5,000.
[0130] The amine having a molecular weight of 500 or more preferably includes an amine having a molecular weight of 1000 or more. In this case, an amine having a molecular weight of 1,000 or more and an amine having a molecular weight of 500 or more and less than 100 may be used in combination. The proportion of amines having a molecular weight of 1000 or more in amines having a molecular weight of 500 or more is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and is preferably 100% by mass or less.
[0131] <Silicone surfactant> The electron beam curable resin composition preferably further contains at least one silicone surfactant, which improves the image quality and further suppresses migration. Here, the silicone surfactant is a surfactant containing a siloxane structure. Examples of the silicone surfactant include BYK-UV3500, 3505, 3510, 3530, 3570, 3575, 3576, 3760, 378, 375, 306, 333, 377, 330, 307, 342, 302, 300, 331, 325, 320, 315N, 326, and 322 (all manufactured by BYK); TEGORad 2100, 2200, 2250, 2300, 2500, 2600, 2700, 2010; TEGOGlide 100, 110, 130, 406, 410, 411, 415, 420, 432, 435, 440, 450, 482, A115, B1484, ZG400; and TEGOFlow 300, 370, 425, ATF2, ZFS 460 (all manufactured by Evonik).
[0132] The content of the silicone surfactant is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and further preferably 1% by mass or more, based on the total amount of the electron beam curable resin composition. The upper limit of the content of the silicone surfactant is preferably 10% by mass or less, and more preferably 5% by mass or less, based on the total amount of the electron beam curable resin composition.
[0133] <Other surfactants> The electron beam curable resin composition may further contain at least one other surfactant other than the silicone-based surfactant.
[0134] The type of the other surfactant is not particularly limited, and may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. Examples of other surfactants include acrylic surfactants and fluorine-based surfactants.
[0135] The acrylic surfactant is a surfactant containing a structure derived from an acrylic monomer. Examples of the acrylic surfactant include BYK361N, BYK350, BYK356, and BYK-UV3535 (all manufactured by BYK).
[0136] The fluorosurfactant is a surfactant containing a perfluoroalkyl group. Examples of the fluorosurfactant include Megafac F-114, F-251, F-253, F-281, F-410, F-477, F-510, F-551, F-552, F-553, F-554, F-555, F-556, F-557, F-558, F-559, F-560, F-561, F-562, F-563, Examples of such dyes include F-565, F-568, F-569, F-570, F-572, F-574, F-575, F-576, R-40, R-40-LM, R-41, R-94, RS-56, RS-72-K, RS-75, RS-76-E, RS-76-NS, RS-78, RS-90, and DS-21 (all manufactured by DIC Corporation).
[0137] <Other ingredients> The electron beam curable resin composition may contain other components in addition to the above components, as necessary, such as a sensitizer, a co-sensitizer, a polymerization inhibitor, an ultraviolet absorber, an antioxidant, a discoloration inhibitor, a conductive salt, an organic solvent, and a basic compound.
[0138] <Physical Properties> The pH of the electron beam curable resin composition is preferably 7 or more, more preferably 7.5 or more, and is preferably 10 or less, more preferably 9.5 or less, from the viewpoint of improving the ejection property when the electron beam curable resin composition is applied by an inkjet method. The pH is measured at 25° C. using a pH meter, for example, a pH meter manufactured by Toa DKK Corporation (model number "HM-31").
[0139] The viscosity of the electron beam curable resin composition is preferably 0.5 mPa·s or more, more preferably 2 mPa·s or more, even more preferably 3 mPa·s or more, and is preferably 30 mPa·s or less, more preferably 20 mPa·s or less, even more preferably 15 mPa·s or less, and particularly preferably 10 mPa·s or less. The viscosity is measured at 25°C using a viscometer, for example, a TV-22 viscometer manufactured by Toki Sangyo Co., Ltd.
[0140] The surface tension of the electron beam curable resin composition is preferably 20 mN / m or more, more preferably 25 mN / m or more, and is preferably 60 mN / m or less, more preferably 50 mN / m or less, and further preferably 45 mN / m or less. The surface tension is measured at 25° C. using a surface tensiometer, for example, an automatic surface tensiometer (product name “CBVP-Z”) manufactured by Kyowa Interface Science Co., Ltd., by a plate method.
[0141] The surface layer can be formed by applying the electron beam curable resin composition to the outer surface of the substrate by an inkjet method, and then irradiating the electron beam curable resin composition with an electron beam to polymerize the polymerizable compound in the electron beam curable resin composition to form a cured product.
[0142] The method of applying the electron beam curable resin composition by the inkjet method (hereinafter also referred to as the inkjet recording method) is not particularly limited, and a known method can be used. Examples of the inkjet recording method include a charge control method that uses electrostatic attraction to eject the electron beam curable resin composition, a drop-on-demand method (pressure pulse method) that uses the vibration pressure of a piezoelectric element, an acoustic inkjet method that converts an electric signal into an acoustic beam and irradiates the electron beam curable resin composition to eject the electron beam curable resin composition using radiation pressure, and a thermal inkjet (Bubble Jet (registered trademark)) method that heats the electron beam curable resin composition to form bubbles and uses the resulting pressure.
[0143] Inkjet heads used in inkjet recording methods include a shuttle method, in which a short serial head is used and recording is performed while the head is scanned in the width direction of the substrate, and a line method, in which a line head is used in which recording elements are arranged to correspond to the entire area of one side of the substrate.
[0144] In the line method, a pattern can be formed on the entire surface of the substrate by scanning the substrate in a direction intersecting the arrangement direction of the recording elements, and a transport system such as a carriage for scanning a short head is not required. In addition, the line method does not require complex scanning control of the carriage movement and the substrate, and only the substrate moves, so a faster recording speed can be achieved compared to the shuttle method.
[0145] The droplet volume of the electron beam curable resin composition ejected from the inkjet head is preferably 1 pL (picoliter) or more, more preferably 3 pL or more, and is preferably 100 pL or less, more preferably 80 pL or less, and even more preferably 50 pL or less.
[0146] The electron beam irradiation can be carried out using an electron beam irradiation device.
[0147] The conditions for irradiation with the electron beam are not particularly limited. The acceleration voltage in electron beam irradiation is preferably 50 kV or more, and preferably 200 kV or less, more preferably 110 kV or less. The dose of electron beam irradiation is preferably 10 kGy or more, more preferably 30 kGy or more, and is preferably 100 kGy or less, more preferably 90 kGy or less. The processing speed in the electron beam irradiation is, for example, 1 m / min or more and 200 m / min or less.
[0148] The electron beam irradiation may be performed in an environment with an oxygen concentration of 20% by volume or less (more preferably less than 20% by volume, and even more preferably 5% by volume or less), which suppresses polymerization inhibition caused by oxygen and further suppresses migration.
[0149] The environment with an oxygen concentration of less than 20% by volume is preferably one in the presence of an inert gas (eg, nitrogen gas, argon gas, and helium gas).
[0150] The application of the electron beam curable resin composition to the substrate and curing by irradiation with electron beams may be performed once or multiple times. By adjusting the number of times, the thickness of the surface layer formed on the outer surface of the substrate can be adjusted. The thickness of the surface layer is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 8 μm or more, and is preferably 35 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. By making the thickness of the surface layer equal to or greater than a certain level, the heat resistance of the surface layer can be improved, whereas by making the thickness of the surface layer equal to or less than a certain level, the tearability can be improved.
[0151] (Sealant layer) The sealant layer is composed of a resin composition mainly composed of polypropylene. The sealant layer contains the same type of resin material as the oriented polypropylene substrate, i.e., polypropylene as the main component. This allows the laminate and the packaging bag to be made of a single material (mono-material). In other words, after collecting used packaging bags, there is no need to separate the substrate and the sealant layer, improving the recyclability of the packaging bag.
[0152] The sealant layer may have a single layer structure or a multi-layer structure. An embodiment of the sealant layer having a multi-layer structure includes a two-layer structure having a first layer that serves as a seal layer and a second layer that serves as a core layer. An embodiment of the sealant layer having a multi-layer structure includes a three-layer structure having a first layer that serves as a seal layer, a second layer that serves as a core layer, and a third layer that serves as a surface layer located on the first adhesive layer side.
[0153] The content of polypropylene in the sealant layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more. A laminate having such a sealant layer has, for example, excellent recyclability.
[0154] Examples of polypropylene include homopolypropylene, random polypropylene such as propylene-α-olefin random copolymer, and block polypropylene such as propylene-α-olefin block copolymer. The details of α-olefin are as described above. From the viewpoint of heat sealability, the density of polypropylene is, for example, 0.88 g / cm 3 More than 0.92g / cm 3 The density is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.). From the viewpoint of reducing the environmental load, biomass-derived polypropylene and / or recycled polypropylene may be used. The sealant layer may contain the above-mentioned additives.
[0155] The thickness of the sealant layer is preferably 5 μm or more, more preferably 10 μm or more, and also preferably 200 μm or less, more preferably 150 μm or less, for example, 10 μm or more and 200 μm or less. A laminate having a sealant layer with a certain thickness or more has excellent seal strength, for example. A laminate having a sealant layer with a certain thickness or less has excellent processability, for example. When a pouch (particularly a retort pouch) is produced from the laminate, the thickness of the sealant layer is preferably 20 μm or more, and also preferably 100 μm or less.
[0156] The sealant layer can be produced, for example, by a conventional method. The sealant layer can be obtained by mixing the above-mentioned materials by a conventional method and forming the resulting mixture into a film by a conventional method. The sealant layer is preferably a film obtained by extrusion molding. The extrusion molding is preferably performed by a T-die method or an inflation method. Specifically, the material constituting the sealant layer is dried as necessary, and then fed to a melt extruder heated to a temperature equal to or higher than the melting point of the material to melt the material, and extruded into a film shape from a die such as a T-die, and the extruded film-like material is rapidly cooled and solidified by a rotating cooling drum or the like, thereby forming the sealant layer.
[0157] As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose. The melt temperature when extruded from the melt extruder is preferably 200° C. or higher, more preferably 220° C. or higher, and is preferably 300° C. or lower, more preferably 270° C. or lower.
[0158] When the sealant layer has a single-layer structure, the composite elastic modulus of the sealant layer is preferably 900 MPa or less, more preferably 830 MPa or less, even more preferably 700 MPa or less, and also preferably 300 MPa or more, more preferably 400 MPa or more, even more preferably 500 MPa or more, for example, 300 MPa or more and 900 MPa or less. A packaging bag produced using a laminate having a sealant layer with a composite elastic modulus within the above range tends to have excellent impact resistance, and therefore excellent bag drop-breakage resistance.
[0159] When the sealant layer has a two-layer structure having a first layer and a second layer, the composite elastic modulus of the second layer, which is the core layer, is preferably 900 MPa or less, more preferably 830 MPa or less, even more preferably 700 MPa or less, and also preferably 300 MPa or more, more preferably 400 MPa or more, even more preferably 500 MPa or more, for example, 300 MPa or more and 900 MPa or less. A packaging bag produced using a laminate having a sealant layer in which the composite elastic modulus of the second layer is within the above range tends to have excellent impact resistance, and therefore excellent bag breakage resistance due to dropping. The composite elastic modulus of the first layer, which is the seal layer, is preferably 800 MPa or more, more preferably 900 MPa or more, even more preferably 1000 MPa or more, and is preferably 2500 MPa or less, more preferably 2000 MPa or less, even more preferably 1500 MPa or less, for example, 800 MPa or more and 2500 MPa or less. A sealant layer having a composite elastic modulus of the first layer within the above range has excellent heat sealability at low temperatures.
[0160] When the sealant layer has a three-layer structure having a first layer, a second layer, and a third layer, the composite elastic modulus of the third layer, which is the surface layer, is preferably 800 MPa or more, more preferably 900 MPa or more, even more preferably 1000 MPa or more, and is preferably 2500 MPa or less, more preferably 2000 MPa or less, even more preferably 1500 MPa or less, for example, 800 MPa or more and 2500 MPa or less. A sealant layer having a composite elastic modulus of the third layer within the above range has excellent heat sealability at low temperatures. The composite elastic modulus of the first layer and the composite elastic modulus of the second layer are the same as those in the case where the sealant layer has a two-layer structure having a first layer and a second layer.
[0161] The composite elastic modulus of the sealant layer is measured by a nanoindentation method. Specifically, the composite elastic modulus is measured using a nanoindenter with a cross section of the sealant layer of the laminate as a measurement surface. The cross section is obtained by cutting the laminate in the thickness direction.
[0162] The location where the indenter is pressed is near the center in the thickness direction of the sealant layer among the exposed cross sections of the sealant layer. Specifically, when the sealant layer has a single-layer structure, the location is near the center in the thickness direction of the sealant layer. When the sealant layer has a three-layer structure, the positions are 2 μm inward from the interface between the sealant layer and the layer in contact with the sealant layer, near the center in the thickness direction of the sealant layer, and 2 μm inward from the sealing surface. In this case, the position 2 μm inward from the sealing surface corresponds to the first layer (sealing layer), the center corresponds to the second layer (core layer), and the position 2 μm inward from the interface with the adhesive layer corresponds to the third layer (surface layer). When the sealant layer has a structure of two or four or more layers, the vicinity of the center of each layer in the thickness direction of the sealant layer is defined as the vicinity of the center of each layer.
[0163] The measurement conditions are as follows. A Berkovich indenter (triangular pyramid indenter) is used as the indenter of the nanoindenter. The indenter is pressed into the sealant layer from the cross section of the sealant layer up to a load of 30 μN over a period of 3 seconds, and is held in that state for 5 seconds. The load is then removed over a period of 3 seconds, and the maximum load P max , contact projection area A at maximum depth p A load-displacement curve is obtained. From the load-displacement curve obtained, the composite elastic modulus is calculated according to the following formula (1).
[0164]
number
[0165] The measurements are performed at room temperature (23°C). Measurements are performed at five or more points at the same measurement position (the point where the indenter is pressed) on the same cross section. The arithmetic mean value of the five values measured at each measurement position is the composite elastic modulus of each layer that constitutes the sealant layer.
[0166] When the sealant layer contains block polypropylene, the composite modulus of elasticity of the sealant layer can be adjusted by the content of ethylene-propylene rubber (EPR). Specifically, the higher the content of ethylene-propylene rubber (EPR), the lower the composite modulus of elasticity can be, and the lower the content of ethylene-propylene rubber (EPR), the higher the composite modulus of elasticity can be. Furthermore, when the sealant layer contains block polypropylene, the composite elastic modulus of the sealant layer can be adjusted by the content of additives such as polyethylene, elastomer, etc. Specifically, the higher the content of the additive, the lower the composite elastic modulus can be, and the lower the content of the additive, the higher the composite elastic modulus can be.
[0167] From the viewpoint of heat sealability, the sealant layer is preferably an unstretched polypropylene film, and the unstretched polypropylene film can be produced by utilizing, for example, a cast method, a T-die method, an inflation method, or the like. The sealant layer may be subjected to the above-mentioned surface treatment.
[0168] (adhesive layer) The laminate of the present disclosure includes a first adhesive layer between the first substrate and the sealant layer. When the laminate of the present disclosure includes a second substrate in addition to the first substrate, the laminate of the present disclosure includes a first adhesive layer between the first substrate and the second substrate, and a second adhesive layer between the second substrate and the sealant layer. By providing the first adhesive layer and the second adhesive layer, the laminate strength between the layers can be improved. Hereinafter, the first adhesive layer and the second adhesive layer will be collectively referred to simply as "adhesive layer".
[0169] The adhesive layer may be an adhesive layer formed by applying an adhesive to the surface of the layer to be laminated and drying it when two layers are bonded together by dry lamination. Examples of adhesives that can be used in the adhesive layer include one-component or two-component cured or non-cured vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, rubber, and other solvent-based, solventless, water-based, or emulsion-type adhesives. Among these, it is preferable to use a solventless adhesive from the viewpoint of reducing the amount of solvent remaining in a packaging bag produced using the laminate. The adhesive can be applied to the coating surface of the layer constituting the laminate by, for example, a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fountain method, a transfer roll coating method, or other methods. The coating amount is 0.1 g / m 2 More than 10g / m 2 Less than 1g / m (dry state) is preferable. 2 More than 5g / m 2 The following (dry state) is more preferred:
[0170] The adhesive layer may also be an anchor coat layer formed by applying an anchor coat agent to the surface of the layer to be laminated and drying it when laminating a thermoplastic resin layer or the like by melt extrusion lamination. The anchor coating agent that can be used for the anchor coating layer may be any resin with a heat resistance of 135°C or higher, such as a vinyl modified resin, an epoxy resin, a urethane resin, or a polyester resin, but is particularly preferably an anchor coating agent that is made of a polyacrylic or polymethacrylic resin having two or more hydroxyl groups in the structure and an isocyanate compound as a curing agent. A silane coupling agent may be used in combination with this as an additive, and soluble nitrocellulose may be used in combination to improve heat resistance.
[0171] The adhesive layer may be an adhesive resin layer used when bonding two layers together by sand lamination or in melt extrusion lamination. Examples of thermoplastic resins that can be used for the adhesive resin layer include polyethylene-based resins, polypropylene-based resins, or cyclic polyolefin-based resins, or copolymer resins, modified resins, or mixtures (including alloys) that contain these resins as their main components. Examples of polyolefin resins include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), polypropylene (PP), ethylene-α-olefin copolymers polymerized using a metallocene catalyst, random or block copolymers of ethylene and polypropylene, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-maleic acid copolymer, ionomer resins, and acid-modified polyolefin resins obtained by modifying the above-mentioned polyolefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid in order to improve adhesion between layers. In addition, resins obtained by graft-polymerizing or copolymerizing unsaturated carboxylic acids, unsaturated carboxylic anhydrides, and ester monomers with polyolefin resins can be used. These materials can be used alone or in combination of two or more. As the cyclic polyolefin-based resin, for example, cyclic polyolefins such as ethylene-propylene copolymer, polymethylpentene, polybutene, polynorbornene, etc. can be used. These resins can be used alone or in combination of two or more. In addition, as the above-mentioned polyethylene-based resin, those using the above-mentioned biomass-derived ethylene as a monomer unit can also be used.
[0172] The adhesive resin layer may contain a material derived from biomass or may contain a material derived from fossil fuels. When the adhesive resin layer contains a material derived from biomass, it may contain a biomass polyolefin, which is a polymer of a monomer containing ethylene derived from biomass.
[0173] When the adhesive resin layer contains a biomass polyolefin, a suitable biomass polyolefin is a biomass-derived low-density polyethylene (product name: SBC818, density: 0.918 g / cm) manufactured by Braskem. 3 , MFR: 8.1 g / 10 min, biomass content 95%), Braskem biomass-derived low-density polyethylene (product name: SPB681, density: 0.922 g / cm 3 , MFR: 3.8g / 10min, biomass degree 95%).
[0174] In the present disclosure, it is preferable that the first substrate is in contact with the first adhesive layer. For example, it is preferable that the inner surface of the first substrate is not printed, and that no printed layer is provided between the first substrate and the first adhesive layer. This improves the adhesion between the first substrate and the first adhesive layer, and improves the lamination strength between the first substrate and the second substrate or the sealant layer bonded by the first adhesive layer.
[0175] (packaging bag) The packaging bag of the present disclosure is characterized by including the laminate of the present disclosure. The shape of the packaging bag is not particularly limited, and may be a shape formed by joining two laminates as shown in FIG.
[0176] In one embodiment, a packaging bag can be produced by folding the laminate of the present disclosure in half, overlapping the laminate so that the sealant layer is on the inside, and heat-sealing the ends. In another embodiment, the packaging bag can also be produced by overlapping two laminates with their sealant layers facing each other, and heat sealing the ends thereof. In the figure, the shaded areas indicate the heat-sealed areas.
[0177] The heat sealing method is not particularly limited, and can be performed by known methods such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.
[0178] In one embodiment, the packaging bag has a stand-up pouch shape having a body and a bottom, as shown in FIG.
[0179] A stand-up pouch-shaped packaging bag can be produced by heat-sealing the laminate of the present disclosure into a cylindrical shape with the sealant layer on the inside to form a body, and then folding another laminate into a V shape with the heat-seal layer on the inside, sandwiching it from one end of the body, and heat-sealing it to form a bottom.
[0180] The contents filled in the packaging bag are not particularly limited, and may be liquid, powder, or gel. In addition, the contents may be food or non-food. After filling the contents, the opening can be heat sealed to form a packaging bag. EXAMPLES
[0181] The laminate and packaging bag of the present disclosure will be described in more detail below with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0182] <Preparation of Pigment Dispersion> The components shown in the composition of the cyan dispersion below were placed in a dispersing machine, Motor Mill M50 (manufactured by Eiger), and dispersed using zirconia beads with a diameter of 0.65 mm at a peripheral speed of 9 m / s for 4 hours to obtain a cyan pigment dispersion. Magenta, yellow, black and white dispersions were prepared in the same manner.
[0183] (Composition of Cyan Dispersion) IRGALITE BLUE GLVO (cyan pigment, manufactured by BASF Japan) …30 parts by mass SR9003 (multifunctional polymerizable compound, propoxylated (2) neopentyl glycol diacrylate, manufactured by Sartomer) …62 parts by mass SOLSPERSE32000 (dispersant, manufactured by Noveon) …8 parts by mass
[0184] (Magenta Dispersion Composition) CINQUASIA MAGENTA RT-355-D (magenta pigment, manufactured by BASF Japan) …30 parts by mass SR9003 (multifunctional polymerizable compound, propoxylated (2) neopentyl glycol diacrylate, manufactured by Sartomer) …60 parts by mass SOLSPERSE32000 (dispersant, manufactured by Noveon) …10 parts by mass
[0185] (Yellow Dispersion Composition) ·NOVOPERM YELLOW H2G (yellow pigment, manufactured by Clariant) …30 parts by mass SR9003 (multifunctional polymerizable compound, propoxylated (2) neopentyl glycol diacrylate, manufactured by Sartomer) …60 parts by mass SOLSPERSE32000 (dispersant, manufactured by Noveon) …10 parts by mass
[0186] (Composition of Black Dispersion) SPECIAL BLACK 250 (black pigment, Orion Engineered Carbons) …40 parts by mass SR9003 (multifunctional polymerizable compound, propoxylated (2) neopentyl glycol diacrylate, manufactured by Sartomer) …50 parts by mass SOLSPERSE32000 (dispersant, manufactured by Noveon) …10 parts by mass
[0187] (Composition of White Dispersion) KRONOS 2300 (white pigment, manufactured by KRONOS) …50 parts by mass SR9003 (multifunctional polymerizable compound, propoxylated (2) neopentyl glycol diacrylate, manufactured by Sartomer) …46.5 parts by mass SOLSPERSE41000 (dispersant, manufactured by Noveon) …3.5 parts by mass
[0188] <Preparation of Electron Beam Curable Resin Composition> The components shown in Table 1 were mixed and stirred to prepare cyan ink, magenta ink, yellow ink, black ink, and white ink as electron beam curable resin compositions.
[0189] The numerical values in the columns for each component in Table 1 indicate parts by mass, and a blank space indicates that the corresponding component is not contained. Details of each component in Table 1 are as follows. · SR341 … Multifunctional polymerizable compound, 3-methyl-1,5-pentanediol diacrylate, manufactured by Sartomer. A-200: Polyfunctional polymerizable compound, polyethylene glycol (200) diacrylate, manufactured by Sartomer. · Viscoat #200: Monofunctional polymerizable compound, cyclic trimethylolpropane formal acrylate (CTFA), manufactured by Osaka Organic Chemical Industry Co., Ltd. · 4-HBA: Monofunctional polymerizable compound, 4-hydroxybutyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd. Speedcure 7010: Hydrogen abstraction initiator with a molecular weight of 1,899, a thioxanthone compound, manufactured by Lambson. Genomer 5271: Amine with molecular weight of 2300, manufactured by IGM Resins BV. UV-22: Polymerization inhibitor, Irgastab® UV-22, Poly[oxy(methyl-1,2-ethanediyl)], alpha, alpha', alpha'-1,2,3-propanetriyltris[omega-[(1-oxo-2-propen-1-yl)oxy]-, 2,6-bis(1,1-dimethylethyl)-4-(phenylenemethylene)cyclohexa-2,5-dien-1-one, manufactured by BASF. ·BYK-378 … Silicone surfactant (polyether modified polydimethylsiloxane), manufactured by BYK Chemie.
[0190] [Table 1]
[0191] [Example 1] As the first substrate, a biaxially oriented polypropylene film (product name: P2171, manufactured by Toyobo Co., Ltd.) having a thickness of 20 μm was prepared. As a second base material, a transparent vapor-deposited stretched polypropylene film (product name: IBOPP-RA, manufactured by Dai Nippon Printing Co., Ltd.) having a thickness of 20 μm was prepared. As a sealant layer, an unstretched polypropylene film (product name: ET-20, manufactured by Okamoto Corporation) having a thickness of 60 μm was prepared. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied to one surface (the surface that would become the inner side) of the first substrate by gravure roll coating, and the surface that would become the inner side of the first substrate and the surface (the surface that would become the outer side) of the second substrate on which the transparent deposition was formed were bonded together. The thickness of the adhesive layer that was the first adhesive layer was 2 μm. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied to the other surface (the surface that would become the inner side) of the second substrate by gravure roll coating, and the surface that would become the inner side of the second substrate was bonded to one surface of the sealant layer. The thickness of the adhesive layer that was the second adhesive layer was 2 μm. In this manner, a laminate raw sheet A was produced in which the first base material, the first adhesive layer, the second base material, the second adhesive layer, and the sealant layer were laminated in this order. White ink was applied to the outer surface of the first substrate by an inkjet method, and then the white ink was polymerized by irradiating it with an electron beam to form a surface layer made of a cured product of the white ink on the outer surface of the first substrate. The thickness of the surface layer was 8 μm. In this manner, the laminate of Example 1 was produced.
[0192] [Example 2] As the first substrate, a biaxially oriented polypropylene film (product name: P2161, manufactured by Toyobo Co., Ltd.) having a thickness of 20 μm was prepared. As in Example 1, a transparent vapor-deposited stretched polypropylene film (product name: IBOPP-RA, manufactured by Dai Nippon Printing Co., Ltd.) having a thickness of 20 μm was prepared as the second base material. As in Example 1, an unstretched polypropylene film (product name: ET-20, manufactured by Okamoto Corporation) having a thickness of 60 μm was prepared as a sealant layer. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied to one surface (the surface that would become the inner side) of the first substrate by gravure roll coating, and the surface that would become the inner side of the first substrate and the surface (the surface that would become the outer side) of the second substrate on which the transparent deposition was formed were bonded together. The thickness of the adhesive layer that was the first adhesive layer was 2 μm. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied to the other surface (the surface that would become the inner side) of the second substrate by gravure roll coating, and the surface that would become the inner side of the second substrate was bonded to one surface of the sealant layer. The thickness of the adhesive layer that was the second adhesive layer was 2 μm. In this manner, a laminate raw sheet B was produced in which the first base material, the first adhesive layer, the second base material, the second adhesive layer, and the sealant layer were laminated in this order. A laminate of Example 2 was produced in the same manner as in Example 1, except that the laminate raw film B was used instead of the laminate raw film A.
[0193] [Example 3] The laminate of Example 3 was produced in the same manner as Example 1, except that a solvent-based adhesive (product name: RU77T / H-7, manufactured by Rock Paint Co., Ltd.) was used instead of a solventless adhesive as the adhesive for bonding the first substrate to the second substrate and the second substrate to the sealant layer, and the thicknesses of the first adhesive layer and the second adhesive layer were 3 μm.
[0194] [Example 4] As the first base material, a transparent vapor-deposited stretched polypropylene film (product name: IBOPP-RA, manufactured by Dai Nippon Printing Co., Ltd.) having a thickness of 20 μm was prepared, similar to the second base material in Example 1. As in Example 1, an unstretched polypropylene film (product name: ET-20, manufactured by Okamoto Corporation) having a thickness of 60 μm was prepared as a sealant layer. A solvent-free adhesive (product name: RN-920 / HN-920, manufactured by Rock Paint Co., Ltd.) was applied by gravure roll coating to the surface of the first substrate on which the transparent deposition was formed (the surface that would become the inner side), and the surface of the first substrate on which the transparent deposition was formed and one surface of the sealant layer (the surface that would become the outer side) were bonded together to produce laminate original sheet C. The thickness of the adhesive layer, which was the first adhesive layer, was 2 μm. A laminate of Example 2 was produced in the same manner as in Example 1, except that the laminate raw fabric C was used instead of the laminate raw fabric A.
[0195] [Example 5] Yellow ink, cyan ink and black ink were further applied to the laminate of Example 1, and an image consisting of four colors, white, yellow, cyan and black, was formed on the surface layer. Specifically, yellow ink was applied by an inkjet method to the outer surface (surface to which white ink was applied) of the laminate of Example 1, and then the yellow ink was polymerized by irradiating with an electron beam. Cyan ink was applied by an inkjet method to the surface to which yellow ink was applied, and then the cyan ink was polymerized by irradiating with an electron beam. Black ink was applied by an inkjet method to the surface to which cyan ink was applied, and then the black ink was polymerized by irradiating with an electron beam. The thickness of the surface layer consisting of the cured products of the white ink, yellow ink, cyan ink, and black ink was 20 μm. In this manner, the laminate of Example 5 was produced.
[0196] [Example 6] Magenta ink was further applied to the laminate of Example 5, and an image consisting of five colors, white, yellow, magenta, cyan and black, was formed on the surface layer. Specifically, yellow ink was applied by an inkjet method to the outer surface (surface to which white ink was applied) of the laminate of Example 1, and then the yellow ink was polymerized by irradiating with an electron beam. Magenta ink was applied by an inkjet method to the surface to which yellow ink was applied, and then the magenta ink was polymerized by irradiating with an electron beam. Cyan ink was applied by an inkjet method to the surface to which magenta ink was applied, and then the cyan ink was polymerized by irradiating with an electron beam. Black ink was applied by an inkjet method to the surface to which cyan ink was applied, and then the black ink was polymerized by irradiating with an electron beam. The thickness of the surface layer consisting of the cured products of the white ink, yellow ink, magenta ink, cyan ink, and black ink was 28 μm. In this manner, the laminate of Example 6 was produced.
[0197] [Example 7] A laminate of Example 7 was produced in the same manner as in Example 6, except that the amount of ink applied was increased and the thickness of the surface layer was set to 32 μm.
[0198] [Comparative Example 1] A laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that the surface layer was not formed. The laminate of Comparative Example 1 had the same structure as the laminate raw sheet A produced in Example 1.
[0199] [Comparative Example 2] A laminate of Comparative Example 2 was produced in the same manner as in Example 2, except that the surface layer was not formed. The laminate of Comparative Example 2 had the same structure as the laminate raw sheet B produced in Example 2.
[0200] [Comparative Example 3] A laminate of Comparative Example 2 was produced in the same manner as in Example 4, except that the surface layer was not formed. The laminate of Comparative Example 3 had the same structure as the laminate raw sheet C produced in Example 4.
[0201] [Comparative Example 4] As in Example 1, a biaxially oriented polypropylene film (product name: P2171, manufactured by Toyobo Co., Ltd.) having a thickness of 20 μm was prepared as the first substrate. As in Example 1, a transparent vapor-deposited stretched polypropylene film (product name: IBOPP-RA, manufactured by Dai Nippon Printing Co., Ltd.) having a thickness of 20 μm was prepared as the second base material. As in Example 1, an unstretched polypropylene film (product name: ET-20, manufactured by Okamoto Corporation) having a thickness of 60 μm was prepared as a sealant layer. A gravure printing ink (product name: Finart BM, manufactured by DIC Graphics Co., Ltd.) was applied to one surface (the surface that would become the inner side) of the first substrate by a gravure roll coating method to form a printed layer. The thickness of the printed layer when dried was 1 μm. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied onto the printed layer by gravure roll coating, and the surface of the first substrate on which the printed layer was formed was bonded to the surface of the second substrate on which the transparent deposition was formed (the surface that would become the outside). The thickness of the adhesive layer, which was the first adhesive layer, was 2 μm. A solvent-free adhesive (product name: XT-020A / XH-020B, manufactured by Mitsui Chemicals, Inc.) was applied to the other surface (the surface that would become the inner side) of the second substrate by gravure roll coating, and the surface that would become the inner side of the second substrate was bonded to one surface of the sealant layer. The thickness of the adhesive layer that was the second adhesive layer was 2 μm. In this manner, a laminate of Comparative Example 4 was produced. The laminate of Comparative Example 4 had the same configuration as the laminate of Comparative Example 1, except that a printed layer was provided between the first substrate and the first adhesive layer.
[0202] [Comparative Example 5] As the first base material, a transparent vapor-deposited stretched polypropylene film (product name: IBOPP-RA, manufactured by Dai Nippon Printing Co., Ltd.) having a thickness of 20 μm was prepared, similar to the second base material in Example 1. As in Example 1, an unstretched polypropylene film (product name: ET-20, manufactured by Okamoto Corporation) having a thickness of 60 μm was prepared as a sealant layer. A gravure printing ink (product name: Finart BM, manufactured by DIC Graphics Co., Ltd.) was applied by gravure roll coating to the surface (inner surface) of the first substrate on which the transparent deposition was formed, to form a printed layer. The thickness of the printed layer when dried was 1 μm. A solvent-free adhesive (product name: RN-920 / HN-920, manufactured by Rock Paint Co., Ltd.) was applied onto the printed layer by a gravure roll coating method, and the surface of the first substrate on which the printed layer was formed was bonded to one surface (the outer surface) of the sealant layer. The thickness of the adhesive layer, which was the first adhesive layer, was 2 μm. In this manner, a laminate was produced in Comparative Example 5. The laminate in Comparative Example 5 had the same configuration as the laminate in Comparative Example 3, except that a printed layer was provided between the first substrate and the first adhesive layer.
[0203] [Comparative Example 6] In the same manner as in Example 1, a laminate raw sheet A was prepared. A gravure printing ink (product name: VM-D Medium (K), manufactured by Dainichi Seika Color & Chemicals Mfg. Co., Ltd.) was applied to the outer surface of the first base material by a gravure roll coating method to form a surface layer. The thickness of the surface layer was 1 μm. In this manner, a laminate of Comparative Example 6 was produced.
[0204] [Comparative Example 7] A laminate of Comparative Example 7 was produced in the same manner as in Comparative Example 6, except that laminate raw fabric C produced in the same manner as in Example 4 was used instead of laminate raw fabric A.
[0205] [Comparative Example 8] In the same manner as in Example 1, a laminate raw sheet A was prepared. A water-based ultraviolet-curable inkjet ink (composition: monofunctional monomer 45% by mass, polyfunctional monomer 40% by mass, photopolymerization initiator 10% by mass, carbon black 2% by mass, and other additives 3% by mass) was applied to the outer surface of the first substrate by the inkjet method, and then the ultraviolet-curable inkjet ink was polymerized by irradiating it with ultraviolet light to form a surface layer made of the cured product of the ultraviolet-curable inkjet ink. The thickness of the surface layer was 8 μm. In this manner, a laminate of Comparative Example 8 was produced.
[0206] [Comparative Example 9] A laminate of Comparative Example 9 was produced in the same manner as in Comparative Example 8, except that laminate raw roll C produced in the same manner as in Example 4 was used instead of laminate raw roll A.
[0207] [Laminate strength measurement] The laminates produced in Examples 1 to 7 and Comparative Examples 1 to 9 were cut into 15 mm-wide strips to obtain test pieces. Using a tensile tester (Tensilon universal material testing machine, manufactured by Orientec Co., Ltd.), the laminate strength (N / 15 mm) of the test pieces was measured in accordance with JIS Z1707:2019 at a temperature of 20°C, a relative humidity of 65%, and a peel speed of 50 mm / min at 90° peeling (T-peel method). Specifically, first, a laminate was cut out, and the substrate and the sealant layer were peeled off by 15 mm in advance in the long side direction to prepare a strip-shaped test piece 100 so that the laminate was divided into the sealant layer side B and the substrate side A. Then, as shown in FIG. 5, the already peeled portions of the sealant layer side B and the substrate side A were gripped by the grips 110 of the measuring device. The grips 110 were pulled at a speed of 50 mm / min in opposite directions perpendicular to the surface direction of the portion where the sealant layer side B and the substrate side A are still laminated, and the average value of the tensile stress F in the stable region (see FIG. 6) was measured. The interval S2 between the grips 110 when the pulling started was 30 mm, and the interval S2 between the grips 110 when the pulling ended was 60 mm. FIG. 6 is a schematic diagram showing the change in the tensile stress F with respect to the interval S2 between the grips 110. As shown in Fig. 6, the change in tensile stress F with respect to the spacing S2 passes through a first region R1 and enters a second region R2 where the rate of change is smaller than that of the first region R1. The second region R2 is also called a stable region. The average value of the tensile stress F in the second region R2 was measured for five test pieces 100, and the average value was determined as the laminate strength. The results are shown in Table 2.
[0208] [Heat resistance evaluation] The surface layer of the laminates produced in Examples 1 to 7 and Comparative Examples 6 to 9 was placed face-to-face with the glossy side of the aluminum foil, and heat-sealed for 2 seconds under a pressure of 2 atmospheres at temperatures of 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., and 200° C. For the laminates of Comparative Examples 1 to 5 not including a surface layer, the outer surface of the first base material was placed face-to-face with the glossy side of the aluminum foil, and heat-sealed under the same conditions. For those laminates that were not dissolved by heat sealing, the laminates and the aluminum foil were peeled off after heat sealing, and the presence or absence of the resin adhering to the glossy surface of the aluminum foil was confirmed. According to the following evaluation criteria, the laminate was evaluated for melting during heat sealing and for adhesion of the resin to the glossy surface of the aluminum foil. The results are shown in Table 2. (Evaluation Criteria) A: The laminate did not melt due to heat sealing, and no resin adhered to the glossy surface of the aluminum foil. B: The laminate was dissolved by heat sealing, or even if the laminate was not dissolved, the resin was adhered to the glossy surface of the aluminum foil.
[0209] [Evaluation of bag making suitability and impact resistance] Two sheets of the laminates produced in Examples 1 to 7 and Comparative Examples 1 to 9 were prepared, stacked with their sealant layers facing each other, and heat-sealed three sides at 180°C, 0.1 MPa, and 1 second to produce a flat pouch of B5 size (182 mm x 257 mm). 350 mL of water was poured into the resulting pouch from the opening, and the opening was heat-sealed under the above conditions to hermetically seal the pouch. After the pouches were obtained, the heat seal plate of the bag making machine was visually inspected and the amount of resin adhering to the heat seal plate was confirmed according to the following evaluation criteria. The results are shown in Table 2. (Evaluation Criteria) A: The adhesion of the resin to the heat seal plate was at a level that did not cause any practical problems. B: A large amount of resin adhered to the heat seal plate. The pouch was then dropped repeatedly 10 times from a height of 100 cm to evaluate its impact resistance according to the following evaluation criteria. The results are shown in Table 2. (Evaluation Criteria) A: The pouch did not break. B: The pouch was torn.
[0210] [Evaluation of tearability] A cut was made in each of the laminates produced in Examples 1 to 7 and Comparative Examples 1 to 9, and the laminate was torn by hand from the cut as the starting point, and the hand-tearability was evaluated according to the following evaluation criteria. The results are shown in Table 2. (Evaluation Criteria) A: The laminate could be cut without getting caught, and the surface layer did not crack when torn. B: The laminate could be cut without getting caught, but the surface layer cracked during tearing. C: There was a snag, and the laminate could not be cut without applying excessive force.
[0211] [Evaluation of residual solvents] Two sheets of the laminate produced in Examples 1 to 7 and Comparative Examples 1 to 9 were prepared, stacked with the sealant layer faces facing each other, and the four sides were heat-sealed under conditions of 180°C, 0.1 MPa, and 1 second to produce a flat pouch of B5 size (182 mm x 257 mm). 200 similar pouches were prepared, and the 200 pouches were placed in a plastic bag (product name: Unipack (registered trademark) L-4, manufactured by Nippon Seisakusho Co., Ltd.), sealed, and stored for 72 hours. After storing for 72 hours, the odor inside the plastic bag was checked and evaluated according to the following evaluation criteria. The results are shown in Table 2. (Evaluation Criteria) A: I didn't smell any solvent. B: I smelled a solvent.
[0212] [Evaluation of retort suitability] Two sheets of the laminates prepared in Examples 1 to 7 and Comparative Examples 6 to 9 were prepared, stacked with the sealant layer faces facing each other, and three sides were heat-sealed under conditions of 180°C, 0.1 MPa, and 1 second to prepare a flat pouch of B5 size (182 mm x 257 mm). 100 mL of water was poured into the obtained pouch from the opening, and the opening was heat-sealed under the above conditions to hermetically seal the pouch. The obtained pouch was subjected to retort sterilization under retort conditions of 121° C., 30 minutes, and 0.21 MPa. A 24 mm wide cellophane tape was attached to the surface layer of the laminate after retort sterilization and then peeled off in one go. The presence or absence of ink adhesion to the cellophane tape was evaluated according to the following evaluation criteria. The results are shown in Table 2. (Evaluation Criteria) A: The ink did not stick to the cellophane tape. B: Ink got on the cellophane tape.
[0213] [Evaluation of residual monomers] The laminates produced in Examples 1 to 7 and Comparative Examples 1 to 9 were evaluated according to the following evaluation criteria to determine whether there was a concern about residual monomers in the surface layer after the curing reaction. The results are shown in Table 2. (Evaluation Criteria) A1: Since the surface layer was formed using an electron beam curable resin composition or a gravure printing ink, there was no concern about residual monomers in the surface layer. A2: Since no surface layer was formed, there was naturally no concern about residual monomers in the surface layer. B: Because the surface layer was formed using a water-based ultraviolet-curable inkjet ink containing a polymerization initiator, there was concern about residual monomers in the surface layer.
[0214] [Table 2]
[0215] As is clear from Table 2, the laminates of Examples 1 to 7 had excellent heat resistance of the surface layer, with no resin adhering to the glossy side of the aluminum foil even when heat-sealed at a temperature of 180°C. Also, the laminates of Examples 1 to 7 had excellent bag-making suitability, with less resin adhering to the heat-seal plate during pouch production. Furthermore, the laminates of Examples 1 to 5 had excellent tearability by setting the thickness of the surface layer below a certain level. [Explanation of symbols]
[0216] 10: Laminate 11: Surface layer 12: First base material 13: First adhesive layer 14: Sealant layer 15:Second base material 16:Second adhesive layer 20: Laminate 100: Test piece 110: Grip tool A: Base material side B: Sealant layer F: Tensile stress R1: 1st area R2: 2nd area S2: Interval
Claims
1. A laminate including, in this order, a surface layer, a first substrate, a first adhesive layer, and a sealant layer, the surface layer is composed of a cured product of an electron beam curable resin composition containing a polymerization initiator (A) and a polymerizable compound (B); the polymerization initiator (A) is a hydrogen abstraction type polymerization initiator having a molecular weight of 500 or more, The first substrate comprises a stretched substrate made of a resin composition mainly composed of polypropylene, The sealant layer is made of a resin composition containing polypropylene as a main component.
2. The laminate according to claim 1 , wherein the content of the polymerization initiator (A) in the electron beam curable resin composition is 0.1% by mass or more and 2% by mass or less.
3. The laminate according to claim 1 or 2, wherein the electron beam curable resin composition further contains an amine having a molecular weight of 500 or more.
4. The laminate according to claim 3 , wherein the content of the amine in the electron beam curable resin composition is from 0.1% by mass to 2% by mass.
5. The laminate according to claim 1 or 2, wherein the polymerizable compound (B) comprises a polymerizable compound having one or more (meth)acryloyl groups in the molecule.
6. The laminate according to claim 1 or 2, wherein the electron beam curable resin composition further contains a pigment.
7. The surface layer, the first base material, the first adhesive layer, the second base material, the second adhesive layer, and the sealant layer are provided in this order; The laminate according to claim 1 or 2, wherein the second substrate comprises a stretched substrate made of a resin composition containing polypropylene as a main component.
8. The laminate of claim 7 , wherein the second substrate further comprises an inorganic oxide layer.
9. The laminate according to claim 1 or 2, wherein the first substrate further comprises an inorganic oxide layer.
10. The laminate according to claim 1 or 2, wherein the surface layer has a thickness of 3 μm or more and 35 μm or less.
11. The laminate according to claim 1 or 2, wherein the first substrate is in contact with the first adhesive layer.
12. A packaging bag comprising the laminate according to claim 1 or 2.
Citation Information
Patent Citations
Aligning method, base line measurement method and aligning device
JP2003086484A
Photopolymerizable resin composition
JP2007204543A
Gas barrier film, packaging material, package
JP2009202519A
Inkjet ink composition, inkjet recording method, and printed matter
JP2014162828A
Laminate for packaging material and packaging material
JP2020040253A